Diffuse Matter from Star Forming Regions to Active Galaxies A Volume Honouring John Dyson - Hartquist, T.W.; Hartquist, T.W.; Pittard, J. M.; Pittard, J. M.; Falle, S.A.E.G.; Falle, S.A.E.G. (Astrophysics and Space Science Proceedings, 2007)
John Dyson has contributed to the study of the hydrodynamic processes that govern a wide variety of astrophysical sources which he has helped explain. In this volume dedicated to him, introductory reviews to a number of the key processes and to the sources themselves are given by leading experts. The mechanisms in which the multi-component natures of media affect their dynamics receive particular attention, but the roles of hydromagnetic effects are also highlighted. The importance of cosmic ray moderation and mass transfer between different thermal phases for cosmic ray moderation and mass transfer between different thermal phases for the evolution of flows are amongst the topics treated. The main types of regions considered include those where stars form, the circumstellar environments of evolved stars, the larger scale interstellar structures caused by the mass loss of stars, and those where the lines of AGNs form. The reviews complement one another and together provide a coherent introduction to the astrophysics of diffuse sources suitable for postgraduate students and researchers in astrophysics. Individual reviews stand alone and are suitable for an audience that includes advanced undergraduates doing final year projects.